2008
DOI: 10.1093/pch/13.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Standard concentrations of high-alert drug infusions across paediatric acute care

Abstract: SCs were successfully instituted with computer support, in lieu of 'smart pumps,' across multiple critical care units in a paediatric institution. The initial program is being expanded to 40 continuous infusion drugs, plus paediatric advanced life support bolus medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…There are several studies supported the standardized fixed drug concentration to use them regularly. [16][17][18][19][20] The authors revised all key elements of medication administration safety, and they suggested several solutions to overcome all gap and weak point with the devices. For instance, use premixed fixed concentration medication use electronic smart infusion The lowest scores items 104 Nurses are notified whenever first dose or stat medications are delivered to the unit when they are not otherwise available on the unit (e.g., in an ADC).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies supported the standardized fixed drug concentration to use them regularly. [16][17][18][19][20] The authors revised all key elements of medication administration safety, and they suggested several solutions to overcome all gap and weak point with the devices. For instance, use premixed fixed concentration medication use electronic smart infusion The lowest scores items 104 Nurses are notified whenever first dose or stat medications are delivered to the unit when they are not otherwise available on the unit (e.g., in an ADC).…”
Section: Discussionmentioning
confidence: 99%
“…a combination of any of the previous themes; n = 18). [100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] A detailed summary of each individual study included in the review is presented in Table 2.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…La estandarizació n del tratamiento intravenoso y la centralizació n de su preparació n en los servicios de farmacia de los hospitales constituyen una primera aproximació n clave para mejorar este proceso, ya que minimiza la manipulació n de la medicació n en las plantas y los consiguientes riesgos asociados 38,39 .…”
Section: Las Bombas De Infusió N Inteligentes No Son Inteligentes Porunclassified